The Relationship Between Public Welfare and Information - Voronenko Iryna V. (Bìznes Inform, 2019)
The article is focused on generalization of theoretical positions and approaches to estimate the impact of information on public welfare. There are presented examples of the relationship between welfare and information, namely for the consumer and the manufacturer. There is emphasized that the relationship between welfare and information depends on the time of obtaining reliable information, which sometimes involves carrying out specialized research that is practically inaccessible to the average consumer, as well as its reliability. There is emphasized that the impact of information on welfare is determined in two dimensions: consumer expectations, as well as the degree of uncertainty for information. There is investigated the influence of advertising on welfare, the results of which concluded that information benefits increase with increasing scale of production, and as a consequence, a decrease in marginal costs. There is given a list of indicators that are most often used to assess the welfare. There is concluded that GDP per capita depends most strongly on the Government’s competitiveness index, moreover, the increase of this index per unit leads to an increase the GDP per capita by 18, 900 USD.